Effect of fungicidal contamination on survival, morphology, and cellular immunity of Apis mellifera (Hymenoptera: Apidae) - Kaur, Gurleen; Singh, Amandeep; Sharma, Rohit; Thakur, Abhinay; Tuteja, Shushant; Shyamli,; Singh, Randeep (Frontiers in Physiology, 2023)
Pesticide residues have been reported in hive-stored products for long periods. Larvae of honey bees experience oral or contact exposure to these products during their normal growth and development inside the cells. We analyzed various toxicological, morphogenic, and immunological effects of residue-based concentrations of two fungicides, captan and difenoconazole, on the larvae of worker honey bees, Apis mellifera. Selected concentrations (0.08, 0.4, 2, 10, and 50 ppm) of both fungicides were applied topically at a volume of 1 µL/larva/cell as single and multiple exposures. Our results revealed a continuous, concentration-dependent decrease in brood survival after 24 h of treatment to the capping and emergence stages. Compared to larvae with a single exposure, the multiply exposed youngest larvae were most sensitive to fungicidal toxicity. The larvae that survived higher concentrations, especially multiple exposures, showed several morphological defects at the adult stage. Moreover, difenoconazole-treated larvae showed a significantly decreased number of granulocytes after 1 h of treatment followed by an increase after 24 h of treatment. Thus, fungicidal contamination poses a great risk as the tested concentrations showed adverse effects on the survival, morphology, and immunity of larval honey bees.